The Efficacy of Acupuncture in Extracorporeal Shock Wave Lithotripsy - Agah, Mahvash; Falihi, A (Urology Journal, 2009)
Purpose: To evaluate the safety and efficacy of acupuncture in comparison with intravenous (IV) sedation in extracorporeal shock wave lithotripsy (ESWL). Material and Methods: One hundred patients, who were scheduled for ESWL, were divided randomly into two groups of fifty patients (acupuncture and IV sedation). In the first group, acupuncture was carried out with special needles (0.30 Ã— 18 mm), in two points 30 minutes before the procedure: point of 36 from the stomach meridian with an angle of 90 degrees and point of 60 from the urinary bladder meridian with an angle of 90 degrees. In the IV sedation group morphine 0.1 mg/kg was injected intramuscularly 30 minutes and intravenous diazepam 0.1 mg/kg for muscle relaxation and anti-anxiety, one minute before the procedure. The two groups were similar in terms of confounding factors. Pain (scored in 4 levels), blood pressure, heart rate, respiratory rate, and arterial blood oxygen saturation were recorded prior to IV sedation or acupuncture, 30 minutes after each, at the beginning of ESWL, 10 minutes after ESWL, and at the end of the procedure (times 1 to 5). Results: In acupuncture group the pain intensity was less than IV sedation group (for time 3, p=0.019, for time 4, p=0.002, for time 5, p=0.05). Considering the pain incidence (each pain score except zero), there was a significant difference at time 4 (p=0.012). None of the procedures was stopped because of pain and none of the patients experienced complications during operation. Arterial blood oxygen saturation was between 95% and 100% for all of the patients in acupuncture group and recovery time was faster (p<0.0001). Conclusion: Acupuncture is a safe and effective method for analgesia. It has a faster recovery time and economical benefits. It also provides the ability to increase the shock wave voltage. We believe that it is a good alternative for IV sedation in ESWL, particularly in patients with lung and heart disease.